Answer:
By using the distributive property the matched equivalent expressions are
1) -7(-4+x) =28-7x
2) -7(4-x) =-28+7x
3) 7(4+x) =28+7x
4) 7(-4-x) =-28-7x
Explanation:
Given that by using the distributive property to match the given equivalent expressions.
1) Given expression is -7(-4+x)
By Distributive property a(b+c)=ab+ac
-7(-4+x) =(-7)(-4)+(-7)(x)
=28-7x
∴ -7(-4+x) =28-7x
2) Given expression is -7(4-x)
By Distributive property a(b+c)=ab+ac
-7(4-x) =(-7)(4)+(-7)(-x)
=-28+7x
∴ -7(4-x) =-28+7x
3) Given expression is 7(4+x)
By Distributive property a(b+c)=ab+ac
7(4+x) =(7)(4)+(7)(x)
=28+7x
∴ 7(4+x) =28+7x
4) Given expression is 7(-4-x)
By Distributive property a(b+c)=ab+ac
7(-4-x) =(7)(-4)+(7)(-x)
=-28-7x
∴ 7(-4-x) =-28-7x
Hence the matched equivalent expressions are
1) -7(-4+x) =28-7x
2) -7(4-x) =-28+7x
3) 7(4+x) =28+7x
4) 7(-4-x) =-28-7x